A Primary Care Approach to Constipation in Adults with Intellectual and Developmental Disabilities. (15th November 2021) - Mathew, Reshmi; Attarha, Barrett O.; Kallumkal, Govind; Cribbin, Morgan; Izzo, Christopher; Edwards, Linda; Jacob, Rafik
Abstract : Constipation is a condition that is very prevalent and is reported in up to 40 percent of individuals with intellectual and developmental disabilities (IDD). Constipation in this patient population is most commonly secondary to neuromuscular abnormalities, immobility, suboptimal diet, and medication side effects. History taking is frequently limited in adults with IDD due to communication barriers, often leading to a missed diagnosis of constipation. Inadequately treated constipation may lead to adverse effects including behavioral disturbances, fecal impaction, intestinal obstruction, and even death from intestinal perforation and sepsis. As a result, a high index of suspicion must exist for this patient population. Treatment in these patients requires an individualized approach, to reduce the constipation and its associated health complications.